KEDUDUKAN KREDITOR PREFEREN DALAM KEPAILITAN SETELAH PUTUSAN MAHKAMAH KONSTITUSI NOMOR 67/PUU-XI/2013 DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Samuel Aprianto; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In bankruptcy accordance with Article 55 paragraph (1) of Law no. 37/2004 on Bankruptcy and Postponement of Paying off Debt, states that creditors holding material security or commonly called separatist creditors can execute their rights as if bankruptcy did not occur, which means they have separate rights and a higher position than creditors who don’t hold rights material in the distribution of bankrupt assets, especially preferred creditors whose assets are part of bankrupt assets. The results of the study stated that after the Constitutional Court Decision No. 67 / PUU-XI / 2013 which interprets Article 95 of the Manpower Law, the position of separatist creditors who used to be higher than the position of laborers' wages, now below the Wages of Laborers who are preferred creditors. Based on the provisions of Article 1134, it is valid for special creditors who do not hold the right of guarantee to take precedence as long as it is regulated by law to prioritize their payments from creditors holding material security rights holders, because they have a valid reason for prior payment. But the implication of the adoption of the Constitutional Court Decision Number 67 / PUU-XI / 2013 is the reduction of the Security Rights of the separatist creditor as the holder of the right to the object guaranteed to give priority to payment (droit de de preferece) than other creditors (Article 1150 of the Civil Code), and cause legal uncertainty regarding the position of preferred creditors and separatist creditors because the material security asset is not part of the bankrupt assets.Keywords: Secured Creditor-Wages Of Laborers